Hypnotherapy Effectiveness in Bronchoscopy to Control Anxiety, Breathlessness and Cough - Teguh Budi Santosa; Yusup Subagio Sutanto; Debree Septiawan (Jurnal Respirologi Indonesia, 2019)
Background: Patient’s comfort during bronchoscopy is important, as it affects its success and the whole outcome. The short comings of bronchoscopy with general anesthesia are long procedure, high cost, and its complication in respiratory failure patient’s. Hypnosis in various surgery procedures can reduce anxiety. Hypnosis can also be used as a therapy for shortness of breath and chronic cough. This study aimed to analyze the effectiveness of hypnotherapy in controling anxiety, breathing shortness a cough of patient’s undergoing bronchoscopy. Methods: This research is a clinical trial with a quasi-experimental design using the pretest-posttest control group approach using consecutive sampling was performed in patients with lung tumor undergoing bronchoscopy in dr. Moewardi Hospital from July to August 2018. The study subjects were randomized in to hypnotized and non-hypnotized (control groups). Scores of Hospital Anxiety and Depression Scale (HADS), modified Borg, and cough Visual Analog Scale (VAS) were measured before and after bronchoscopy. Results: Thirtyseven lung tumor patient’s undergoing bronchoscopy were included in our study. The intervention groups showed decreased HADS (6,68+8,28) and different significantly compared to control group (p